EFEK KEKERINGAN DAN GANGGUAN ASAP TERHADAP EKOFISIOLOGI DAN PRODUKTIVITAS TANAMAN KELAPA SAWIT DI SUMATRA SELATAN - Syarovy, Muhdan; Pradiko, Iput; Listia, Eka; Darlan, Nuzul Hijri; Hidayat, Fandi; Winarna, Winarna; Rahutomo, Suroso (Jurnal Penelitian Kelapa Sawit, 2017)
Prolonged dry season, land fire, and haze disturbance occurred during El Niño 2015 in Indonesia. A study had been conducted to identify impacts of prolonged dry season and haze disturbance on ecophysiology of oil palm in Dawas Estate, South Sumatra. The study was conducted by collecting data of precipitation, visibility, oil palm fronds addition, rate of photosynthesis, Photosinthetically Active Radiation (PAR), and Elaeidobius kamerunicus activity on mature and immature palm before, during and after the incidence of drought and haze disturbance. T test was used for statistics analysis. The results showed that water deficit was recorded in July, August, September and October, it was 45, 92, 80, and 148 mm respectively. Dry month (precipitation was ≤ 60 mm) was 2 months, while dry spell occurred 3 times in June to July (33 days), August to September (42 days), and September to October (40 days). Haze disturbance occurred in August to November, it had decreased visibility to 80%. During drought stress and haze disturbance, there was decrease in fronds addition, photosynthesis rate and bunch productivity in following year. In addition, haze disturbance had decreased number of Elaeidobius kamerunicus visitting female flowers up to 95%.